Science Practicum and Mini Edupark School (MES) As Alternatives To Improve Environmental Care Attitude In Philosophy Perspective - Bakhtiar Ardiansyah; Muhammad Sarjan; Aliefman Hakim (Unversitas Muhammadiyah Mataram, 2022)
Abstract: This article aims to describe philosophically related to Science Practicum Activities and Mini Edupark School (MES) facilities which are expected to support future education, especially environmental conservation attitudes. This article uses a qualitative descriptive approach. Philosophically, ontology is obtained an overview related to the nature of the Science Practicum activities and the Mini Edupark School (MES) Facilities. From an epistemological philosophy, we get an overview of the procedures, types of science practicum and how the Mini Edupark School (MES) is implemented in science learning. Philosophically, axiologically, an overview of universal values is obtained from the existence of science practicum activities and the Mini Edupark School (MES), especially towards an attitude of caring for the environment.Abstrak: : Artikel ini bertujuan untuk menggambarkan secara filsafat terkait Kegiatan Praktikum IPA dan sarana Mini Edupark School (MES) yang diharapkan dapat mendukung pendidikan masa depan khususnya sikap konservasi lingkungan. Artikel ini menggunakan pendekatan deskriptif kualitatif. Secara Filsafat ontologi diperoleh gambaran terkait hakekat dari kegiatan Praktikum IPA dan Sarana Mini Edupark School (MES). Secara Filsafat epistimologi diperoleh gambaran terkait prosedur, jenis praktikum IPA dan bagaimana Mini Edupark School (MES) itu dilaksanakan dalam pembelajaran IPA. Secara filsafat aksiologi diperoleh gambaran terkait nilai-nilai universal yang diperoleh dari keberadaan kegiatan praktikum IPA dan Mini Edupark School (MES) khususnya mengarah kepada sikap peduli lingkungan